Inequality and Market Concentration, When Shareholding Is More Skewed Than Consumption - Joshua S. Gans; Andrew Leigh; Martin Schmalz; Adam Triggs (Institute of Labor Economics (IZA), 2018)
Economic theory suggests that monopoly prices hurt consumers but benefit shareholders. But in a world where individuals or households can be both consumers and shareholders, the impact of market power on inequality depends in part on the relative distribution of consumption and corporate equity ownership across individuals or households. The paper calculates this distribution for the United States, using data from the Survey of Consumer Finances and the Consumer Expenditure Survey, spanning nearly three decades from 1989 to 2016. In 2016, the top 20 percent consumed approximately as much as the bottom 60 percent, but had 13 times as much corporate equity. Because ownership is more skewed than consumption, increased mark-ups increase inequality. Moreover, over time, corporate equity has become even more skewed relative to consumption.
Keywords: D42; D43; D61; D63; 330; monopoly; market power; inequality